Kidney transplantation for a patient with refractory childhood-onset ANCA-associated vasculitis. Issue 2 (3rd March 2016) - Kaseda, Koji; Marui, Yuji; Suwabe, Tatsuya; Hoshino, Junichi; Sumida, Keiichi; Hayami, Noriko; Mise, Koki; Tanaka, Kiho; Takaichi, Kenmei; Tomikawa, Shinji; Fujii, Takeshi; Ohashi, Kenichi; et al.
Abstract : A 14-year-old Japanese girl was admitted to our institution for the evaluation of renal dysfunction. Her serum creatinine was 1.1 mg/dL, proteinuria was 1.5 g/day, the urine sediment contained numerous erythrocytes per high-power field, and she was positive for myeloperoxidase anti-neutrophil cytoplasmic antibody (MPO-ANCA). Proteinuria was first noted at the age of 12 years. Renal biopsy showed crescentic glomerulonephritis with slight immunoglobulin A (IgA) deposition. A diagnosis of ANCA-associated vasculitis was made. Immunosuppressive therapy was initiated, including steroid pulse therapy and intravenous cyclophosphamide pulse therapy, but hemodialysis was required after 6 years. Eight months after the patient became anuric and her MPO-ANCA titer became negative, living-related donor kidney transplantation was done from her mother. ANCA became slightly positive 2 years later, but the patient remains stable without proteinuria or hematuria at 4 years after surgery. This case suggests that kidney transplantation can be performed successfully for a patient with refractory childhood-onset ANCA-associated vasculitis, and that remission of vasculitis associated with ANCA negativity at transplantation may contribute to a better renal prognosis in this patient.